Water Quality of Al-Dalmaj Marsh, Iraq - Al-Hemidawi, Faris N.M.; Mohammed, Abbas H.; Al-Saad, Hamid T. (Mesopotamian Journal of Marine Sciences, 2020)
Samples of water were taken during February 2018 to November 2018 at ten stations in Al-Dalmaj Marshes, to cover all the marsh area. Physical and chemical properties including the natural water quality parameters, Total Dissolved Solids (8270-10781 mg/l), Turbidity (2.63-5.72 NTU), Electrical Conductivity (12.92-17.12mS/cm), Total Hardness (3204-4034 mg/l), Water Temperature (18-40 ºC), Air Temperature (20-45 ºC), Salinity (1.72-10.94 PSU), pH (6.98-7.61), Total Alkalinity (396.8-443 mg/l), Calcium (468-607 mg/l), Magnesium (492-687 mg/l), Chloride (2977-4286 mg/l), Sodium (568-1221 mg/l), Potassium (29-84 mg/l), Bicarbonate (137-1210 mg/l) and Sulfates (706-984 mg/l). The above values show the seasonal variations of water variables at the study stations using statistical methods to verify the results, and these results provide important reference information for further study.